Quantum‐Dot Light‐Emitting Diodes for Large‐Area Displays: Towards the Dawn of Commercialization. Issue 14 (3rd March 2017) - Dai, Xingliang; Deng, Yunzhou; Peng, Xiaogang; Jin, Yizheng
Abstract : Quantum dots are a unique class of emitters with size‐tunable emission wavelengths, saturated emission colors, near‐unity luminance efficiency, inherent photo‐ and thermal‐ stability and excellent solution processability. Quantum dots have been used as down‐converters for back‐lighting in liquid‐crystal displays to improve color gamut, leading to the booming of quantum‐dot televisions in consumer market. In the past few years, efficiency and lifetime of electroluminescence devices based on quantum dots achieved tremendous progress. These encouraging facts foreshadow the commercialization of quantum‐dot light‐emitting diodes (QLEDs), which promises an unprecedented generation of cost‐effective, large‐area, energy‐saving, wide‐color‐gamut, ultra‐thin and flexible displays. Here we provide a Progress Report, covering interdisciplinary aspects including material chemistry of quantum dots and charge‐transporting layers, optimization and mechanism studies of prototype devices and processing techniques to produce large‐area and high‐resolution red‐green‐blue pixel arrays. We also identify a few key challenges facing the development of active‐matrix QLED displays. Abstract : The dawn of commercialization for large‐area quantum‐dot light‐emitting‐diode (QLED) displays is coming, as indicated by the recent impressive advancements of both the efficiency and lifetime of QLEDs. The progress in materials chemistry of quantum dots and charge‐transporting layers, device engineering and quenching mechanisms of QLEDs, and patterning techniques to realize high‐resolution arrays of red‐green‐blue pixels is discussed.